Rising Stars in Science and Technology: Luminescent Lanthanide Materials - Bunzli, Jean-Claude G (European journal of inorganic chemistry, 2017)
This essay draws attention to lanthanide luminescence by putting into perspective the sensitization process of f–f emission, the design of highly luminescent lanthanide‐based compounds, and upconversion nanoparticles. A brief overview of the recent advances in some applications, namely lighting, security inks and tags, as well as biological applications, is presented. Lanthanide luminescence is indispensable in numerous high‐technology applications, which range from lighting to displays, telecommunications, security inks and tags, crack detectors, bioanalysis, and bioimaging. Emerging applications are in solar energy conversion, nanothermometry, optical refrigeration, and quantum information processing.